Biotechnology-based Profiling of Lichens and Their Metabolites for Therapeutic Applications - Srivastava, Priyansh; Partha Sarethy, Indira (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2023)
Lichens have been inadequately studied for their medicinal value though recent studies have established them as potential sources of bioactive compounds that show antimicrobial, anticancer, antioxidant and neuroprotective properties. Ethnobotanical studies have shown that Pseudocyphellaria aurata, Usnea bismolliuscula, Usnea longissimi, Xanthoparmelia conspersa, Sulcaria sulcate and Solorina crocea have been used by humans since ancient times as a part of their folk wisdom. Recent studies have shown that metabolites from lichens show promising bioactive properties. This review focuses on the necessity for utilizing a modern biotechnology-based approach for elucidating the role and unrealized potential of lichens. Technologies such as genomics, metagenomics, and proteomics have been applied to a far lesser extent in lichens, but the limited studies have revealed the unrealized potential of lichens in modern therapeutics. We attempt to provide a broad overview of the known and unknown in lichen research – ranging from the metabolite production pathways to the genomics and metagenomics, and further to the proteomics and transcriptomics of lichens, the threads of which need to be pieced together to provide a roadmap for further studies.